2016
DOI: 10.1097/pec.0000000000000366
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Abducens Nerve Paralysis in the Pediatric Emergency Department

Abstract: Other lesions of primary brain tumors causing increased intracranial pressure constitute 50% of the underlying etiology, followed by Guillain-Barre syndrome (14.2%). However, these patients had neurological symptoms signs, in addition to diplopia or SCN paralysis. Patients admitted to pediatric emergency department with acute SCN paralysis should be examined in detail to disclose the underlying etiology especially if they present with additional clinical signs or symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Abducens nerve palsy clinically presents with diplopia, inward deviation of the eye and difficulty with lateral ocular movement. Accompanying symptoms such as headache, vomiting, unstable gait and fever may be present depending on the palsy's etiology (15).…”
Section: Discussionmentioning
confidence: 99%
“…Abducens nerve palsy clinically presents with diplopia, inward deviation of the eye and difficulty with lateral ocular movement. Accompanying symptoms such as headache, vomiting, unstable gait and fever may be present depending on the palsy's etiology (15).…”
Section: Discussionmentioning
confidence: 99%
“…7 Considering that benign abducens nerve palsy in children may be caused by immune-mediated nerve injury, we treated both patients with methylprednisone, gamma globulin, and vitamin B for nerve nutrition, and their clinical symptoms gradually improved. Some studies 3 also claim that the disease itself is self-limited and does not require specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al 2 analyzed the causes of abducens nerve palsy in children and concluded that tumors and related neurosurgery were the most common causes (45%), followed by elevated intracranial pressure (15%), traumatic brain injury (12%), congenital causes (11%), inflammation (7%), other causes (5%), and idiopathic causes (5%). It has also been reported that Guillain-Barre syndrome 3 and upper respiratory infections 3 can lead to abducens nerve palsy. Benign abducens nerve palsy has a low incidence in children, and its diagnosis relies on the exclusion of other diagnoses.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar to adults, isolated sixth (6th) nerve palsy is the most common cranial nerve palsy in the pediatric population [ 1 ]. However, it is far less frequent in children and demands an immediate and thorough investigation, due to potentially devastating common causes in these ages, such as trauma, neoplasms, central nervous system infection, or raised intracranial pressure [ 2 , 3 ]. Benign causes account for just 9 to 14% of all 6th nerve palsies in children [ 4 ].…”
Section: Introductionmentioning
confidence: 99%